2001
DOI: 10.1023/a:1010615215528
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The effects of fiber on colon cancer are controversial. Twenty 5-week old C57BL/6J Apc Min/+ mice were fed for 60 days with a commercial mouse diet (Teklad LM-485) and eight semidefined diets containing 5-10% various fibers and 20% soybean oil. Ten additional C57BL/6J congenic litter-mates were fed each diet to assay colonic SCFA. SCFA, stool bulk, and colonic tumor incidence differed only slightly among the semidefined diets despite variations in fiber content and source. However, food consumption, caloric in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Prevention of colon cancer remains a significant public health issue that is highly associated with genetic and environmental factors such as diet composition [30]. Evidence is emerging that diet and nutrient factors may play an important role in colorectal cancer incidence and progression [31-34].…”
Section: Introductionmentioning
confidence: 99%
“…Prevention of colon cancer remains a significant public health issue that is highly associated with genetic and environmental factors such as diet composition [30]. Evidence is emerging that diet and nutrient factors may play an important role in colorectal cancer incidence and progression [31-34].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that a low-fat diet can prevent colon tumor formation, but the relative risk associated with dietary fat in humans remains unclear. 66 , 67 Our study demonstrates a protective effect of endogenous TSP1 that is sensitive to dietary fat intake. The loss of TSP1 expression that has been documented to result from loss of tumor suppresser genes and activation of oncogenes associated with colon carcinogenesis could contribute to promoting early and late stages of colon tumor formation.…”
Section: Discussionmentioning
confidence: 58%